2020
DOI: 10.1016/j.ajodo.2020.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal implications of surgical-orthodontic treatment of an impacted dilacerated maxillary incisor: A case report with a 2-year follow-up

Abstract: The treatment of an 8-year-old girl with a dilacerated maxillary incisor began in the mixed dentition; a modified palatal arch attached to the molars served as anchorage for the forced eruption of the dilacerated tooth to prevent the intrusion of the adjacent teeth and reduce the risk of root resorption. Two surgical sessions were planned: the first to permit the closed eruption; the second was an apically positioned flap to add attached gingiva to the labial side of the erupting tooth. The result was an optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The root of 21 was selected as the control reference, with the preop root length of 19.60 mm and post-op root length of 19.39 mm (Figure 13). Treatment success of the current case related to root resorption was similar to other reported cases; 2,21,26,28,29 however, the previous studies only qualitatively evaluated the root status on post-operative panoramic radiographs, without quantitative measurements. To the best of current knowledge, this is the first case report that measured and compared the resorption of the dilacerated root using CBCT with the contralateral incisor as the control reference.…”
Section: Treatment Outcome and Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The root of 21 was selected as the control reference, with the preop root length of 19.60 mm and post-op root length of 19.39 mm (Figure 13). Treatment success of the current case related to root resorption was similar to other reported cases; 2,21,26,28,29 however, the previous studies only qualitatively evaluated the root status on post-operative panoramic radiographs, without quantitative measurements. To the best of current knowledge, this is the first case report that measured and compared the resorption of the dilacerated root using CBCT with the contralateral incisor as the control reference.…”
Section: Treatment Outcome and Discussionsupporting
confidence: 82%
“…Treatment time for an impacted dilacerated tooth has varied significantly between 11 and 45 months. 2,[26][27][28][29] The treatment time for the current case was 43 months due to the deep impaction and severe displacement. The influencing factors of treatment time usually include the complexity of the case, the type of malocclusion, and the stage of dental development.…”
Section: Treatment Outcome and Discussionmentioning
confidence: 99%
“…14,15 Orthodontic appliances and techniques designed for this purpose have been proposed specifically for repositioning the impacted teeth on the maxillary arch. [16][17][18][19][20][21][22][23] The surgical procedures performed to expose the impacted teeth should respect the soft tissue as much as possible. In case of submucosal palatal impaction where only soft tissue is involved, the keratinized gingiva must be preserved and an apically positioned flap (APF) should be raised.…”
Section: Discussionmentioning
confidence: 99%
“…The most appropriate orthodontic treatment should be able to simulate the physiological eruption pattern of the permanent teeth that occurs at the center of the alveolar ridge as some authors have already suggested 14,15 . Orthodontic appliances and techniques designed for this purpose have been proposed specifically for repositioning the impacted teeth on the maxillary arch 16‐23 …”
Section: Discussionmentioning
confidence: 99%